Exploring climate migration and environmental security: Türkiye to America and beyond - Tezcan, Neslihan (My University, 2024)
Since all three books were published in 2023, they are foremost among the works that will be useful for those interested in this topic, as they are up-to-date and address current issues on the relationship between climate change, forced migration, and environmental security. Many studies conducted around the world reveal that the effects of climate change will become much more visible both in the world and in Türkiye, especially in the next decade, and that the lives of millions of people will be directly negatively affected. For this reason, it is important to conduct qualitative and quantitative studies on what awaits Türkiye in terms of climate-related risks, especially in terms of migration.
Keywords: Climate Migration; Displacement; Environmental Security